Superhydrophilic polymer surface modification by low energy reactive ion beam irradiation using a closed electron Hall drift ion source - Choi, Won-Kook (ELSEVIER SCIENCE SA, 2007)
A gridless closed electron Hall drift plasma accelerator with very low energy (< 200 eV) and high current density (similar to 1 mA/cm(2)) was adopted for polymer surface modification. Ar, N-2, O-2, and N2O gases were used for the generation of plasma and the ions were irradiated on polyimide and polyvinylidene fluoride with the ion fluence of 5 X 10(15)/cm(2) - 1 X 10(18) /cm(2). By the irradiation of O-2(+) at the very low ion fluence of 5 x 10(15)/cm(2) corresponding to 1 s treatment time, the wetting angle of PI and PVDF were greatly reduced from 78 degrees and 61 degrees to less than 2 degrees and N2O+ ion irradiation showed analogous results. The attainment of superhydrophilic polymer surface can be explained by the formation of hydrophilic group induced by low energy reactive ion beam irradiation. From the results, it is revealed that the very low energy ion beam irradiation can be used as an effective and productive ion source compared with conventional gridded ion source for the enhancement of surface energy of polymer. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: FILM ADHESION; THIN-FILM; AR+ ION; POLYCARBONATE; ENHANCEMENT; WETTABILITY; ENVIRONMENT; PLASMA; PVDF